Exploring Preschool Teachers’ Writing Beliefs and Practices in the Context of Brunei Darussalam - Siti Noorhanida Md Yussof (SEAMEO CECCEP, 2024)
This qualitative study examines preschool teachers' writing beliefs and practices through interviews and thematic analysis. It explores the diverse writing activities used, emphasizing foundational skills like handwriting and spelling. While teachers expressed concerns about readiness to teach writing and the need to boost children's writing motivation, they showed enthusiasm and confidence in their writing capabilities. Recommendations include targeted professional development, a balanced approach to writing instruction, and collaboration among teachers to enhance writing outcomes in preschool settings. This study underscores the importance of supporting preschool teachers in developing effective writing instruction practices for early literacy skills and student writing development.